Quantitative Phase Imaging During Cell Division Based on Dual-Channel Microscopic Interferometry System - Shengde Liu; Dejin Zheng; Jiaosheng Li; Jindong Tian; Liyun Zhong; Xiaoxu Lu (IEEE Photonics Journal, 2020)
Quantitative phase imaging (QPI) during cell division is implemented by ourhomemade dual-channel microscopic interferometry (DCMI) system. A pair of interferograms with a fixed phase shift of π/2 is simultaneously captured by the DCMI system, and two-step phase demodulation algorithm is employed for phase retrieval. By capturing a sequence of paired-interferograms with the DCMI system, we achieve the dynamic QPI during cell division, and then the cellular surface area, volume and the ratio of surface area to volume (RSV) and their variations. Both the reliability and stability of the DCMI system are verified. In addition to maintaining the advantages of optical interferometry, this DCMI system is very suitable for dynamic QPI due to its rapid speed of phase retrieval. Importantly, this DCMI based QPI method will supply a powerful tool for studying the precise mechanism during cell division, differentiation, apoptosis and other dynamic processes.